Effect of pH and sulfate concentration on hydrogen production using anaerobic mixed microflora - Hwang, Jae-Hoon; Choi, Jeong-A; Abou-Shanab, R. A. I.; Bhatnagar, Amit; Min, Booki; Song, Hocheol; Kumar, Eva; Choi, Jaeyoung; Lee, Eung Seok; Kim, Yong Je; Um, Sukkee; Lee, Dae Sung; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The effects of varying sulfate concentrations with pH on continuous fermentative hydrogen production were studied using anaerobic mixed cultures growing on a glucose substrate in a chemostat reactor. The maximum hydrogen production rate was 2.8 L/day at pH 5.5 and sulfate concentration of 3000 mg/L. Hydrogen production and residual sulfate level decreased with increasing the pH from 5.5 to 6.2. The volatile fatty acids (VFAs) and ethanol fractions in the effluent were in the order of butyric acid (HBu) > acetic acid (HAc) > ethanol > propionic acid (HPr). Fluorescence In Situ Hybridization (FISH) analysis revealed the presence of hydrogen producing bacteria (HPB) under all pH ranges while sulfate reducing bacteria (SRB) were present at pH 5.8 and 6.2. The inhibition in hydrogen production by SRB at pH 6.2 diminished entirely by lowering to pH 5.5, at which activity of SRB; is substantially suppressed. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: METHANE-PRODUCING BACTERIA; PRODUCTION WASTE-WATER; REDUCING BACTERIA; FULL-SCALE; REDUCTION; ACIDOGENESIS; TEMPERATURE; INHIBITION; SUBSTRATE; DIGESTION